Peran Pasar Tradisional dalam Meningkatkan Perekonomian Perspektif Ekonomi Islam: Studi Pada Pasar SP 1 Arga Jaya Kabupaten Mukomuko provinsi Bengkulu - Putri lestari, Gita; Hak, Nurul; Afrianty, Nonie (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the role of traditional market traders in improving the community’s economy from an Islamic economic perspective. The research focuses on traders at SP 1 Arga Jaya Market using a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that traditional market traders significantly contribute to the local economy, particularly by providing employment opportunities, increasing income, and ensuring equitable access to basic goods. From the perspective of Islamic economics, trading activities in traditional markets reflect the principles of justice, transparency, and mutual assistance. Nevertheless, several challenges remain, such as limited capital and competition from modern markets. This study highlights that strengthening the role of traditional market traders through the application of Islamic values can serve as a key strategy to promote fair and sustainable economic development.